Effect of Angiography Room Orientation Tour on Anxiety of Patients Awaiting Cerebrovascular Angiography - Kolahi, Zahra; Zandi, Mitra; Esmaeili, Roghayeh; KhabazKhoob, Mehdi (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Cerebrovascular angiography is a method of diagnosing cerebrovascular disorders. Invasive procedures induce anxiety in patients. Poor management of anxiety may be life-threatening for patients. It is the duty of nurses to reduce anxiety. Given the prevalence of anxiety in patients awaiting cerebrovascular angiography and its detrimental complications and also the critical role of nurses in the psychosomatic support of patients and their struggle to reduce anxiety, the use of different methods of patient education such as familiarizing them with diagnostic and therapeutic processes is of utmost significance. This study investigated the effect of orientation tour on anxiety in candidates of cerebrovascular angiography. Methods: In this experimental study, 114 patients awaiting cerebrovascular angiography presenting to Imam Hussein Hospital and Shohadaye Tajrish Hospital in Tehran, capital of Iran, were selected with a convenient sampling method and assigned randomly to either case or control groups. The control group just received routine education in the ward. In contrast, the case group received routine education in the ward and instructions on performing angiography and its pre-, peri-, and post-operative care. Demographics questionnaire and the Depression Anxiety Stress Scale (DASS-21) were used to collect data. Patients’ anxiety was measured twice with this instrument at hospitalization and after the intervention. The gleaned data were analyzed with SPSS21 using independent t-test, Chi-square test, and ANOVA. Results: Distribution of age was the same in both groups (P < 0.11). Independent t-test showed a significant difference in the mean score of anxiety before intervention in the control group (9.2) and case group (7.2) (P = 0.02). This test also indicated a significant difference in the mean score of patients’ anxiety after intervention in both the control group (9.7) and case group (6.7) (P = 0.001). However, using data collected before the orientation tour as the covariate, repeated measures ANOVA showed a significantly more significant reduction of anxiety in the case group. Conclusions: According to our findings, participation in the angiography room orientation tour leads to reduced anxiety in patients awaiting cerebrovascular angiography. The use of this method is advisable for patients before diagnostic and therapeutic processes.